Using Critical Realism to Explain Indeterminacy in Role Behaviour Systematically1. (14th September 2014) - Luke, Darcy; Bates, Stephen
Abstract We demonstrate in this article how critical realism can be used to explain indeterminacy in role behaviour systematically. In so doing, we both rebut various criticisms of critical realism made recently by Kemp and Holmwood and attempt to illustrate the weaknesses and absences of approaches that concentrate unduly on the collection of expectations of (different groups of) actors concerning roles and the behaviour of incumbents. Within a framework that recognises that structure and agency are ontologically distinct but necessarily empirically related entities, we argue that structures should be seen as sources of indeterminacy within role behaviour for at least four reasons: the co‐determination of roles through the intersection of structures; conflicting role expectations caused by contradictions inhering within structures; asymmetries of power within social relations; and asymmetric repetition within structural reproduction/transformation. In light of this discussion of structural sources of indeterminacy, we then go on to demonstrate how critical realism is also able to analyse systematically the agential sources of indeterminacy within role behaviour and expectations through theories of psychobiography and reflexivity. We thus conclude that critical realism contains the conceptual tools required to illuminate the point(s) of intersection between structure, culture and agency which is central to understanding both role behaviour and the plurality of expectations concerning such behaviour.